The Influence of Financial Literacy, Gender, and Lifestyle on Employee Debt Management of PT Adelia Sejahtera Nusantara - Maininda Prasasti; Noni Ardian; Ramadhan Harahap (CV. Doki Course and Training, 2026)
The rapid development of financial technology, particularly online lending (peer-to-peer loans), in Indonesia has significantly improved access to credit; however, it has also given rise to poorly managed debt problems. This study aims to analyze the effects of financial literacy, gender, and lifestyle on the debt management of employees at PT Adelia Sejahtera Nusantara, both partially and simultaneously. This research adopts a quantitative approach with an associative research design. The population of this study consists of all 40 employees of PT Adelia Sejahtera Nusantara, using a saturated sampling technique. The data used are primary data collected through a questionnaire employing a 1–5 Likert scale. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 31, preceded by validity tests, reliability tests, and classical assumption tests. The results indicate that:(1) financial literacy has a positive and significant effect on debt management; (2) gender has no significant effect on debt management; (3) lifestyle has a positive and significant effect on debt management; and (4) simultaneously, the three variables have a significant effect on debt management, with an F-value of 784.786 (p < 0.001) and a predictive power of 78.4% (Adjusted R² = 0.784), leaving only 21.6% explained by other factors.